Strengthening Indonesia’s adolescent anemia policy: a systematic review of global practices - Melisa Yuniarti; Anita Rahmiwati; Suci Destriatania (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2026)
Background: Anemia is a persistent public health challenge in Indonesia, particularly among adolescent girls, with prevalence reaching 48.9% in 2018. Despite school-based iron and folic acid (IFA) supplementation programs, major implementation challenges remain. Objective: To evaluate the implementation of IFA policies for adolescents in Indonesia and to identify global strategies that can strengthen national anemia prevention efforts. Method: A systematic review was conducted following PRISMA guidelines, focusing on studies published between 2019 and 2024. PubMed, Google Scholar, and official Ministry of Health sources were searched using predefined eligibility criteria. Data from eligible studies were synthesized using thematic analysis. Search strings included terms such as: “iron and folic acid supplementation” OR “iron–folic acid” OR “IFA”, combined with “adolescent” OR “school-age girls”, and “policy” OR “program implementation” OR “coverage” OR “adherence”. Results: Five studies met the inclusion criteria. Four main barriers to effective IFA implementation were identified: (1) low adherence due to side effects and misconceptions; (2) logistical weaknesses in tablet distribution; (3) limited stakeholder engagement; and (4) lack of robust monitoring systems. Evidence from other countries shows that school-based education, digital monitoring, and community involvement can improve coverage and compliance. Conclusion: Indonesia’s IFA policy needs strengthening in both structural and behavioral domains. Integrating education, digital tracking, and peer involvement into existing school-based programs may enhance adherence and long-term sustainability.